Tanggung Jawab Lembaga Pemasyarakatan dalam Pembinaan Narapidana Residivis Kajian terhadap UU Pasal 2 No. 22 Tahun 2022 - Moch. Taufik Sanhaji; Ismail Marzuki (AHKAM, 2025)
This study is motivated by the limited specific research on the responsibilities of correctional institutions in rehabilitating recidivist inmates, despite the issue having significant implications for reducing repeat offenses and strengthening the criminal justice system in Indonesia. The objective is to analyze the legal responsibilities of correctional institutions and evaluate the implementation of Article 2 of Law No. 22 of 2022 in the rehabilitation of recidivist inmates. The research employs a normative juridical method with descriptive analysis, using legal documents, legislation, and relevant literature as primary and secondary data sources. Data were collected through document studies and analyzed using legal interpretation and qualitative descriptive techniques. The findings reveal that, normatively, correctional institutions bear legal, moral, and social responsibilities in rehabilitating recidivists. However, implementation is hindered by issues such as overcrowding, limited human resources, inadequate facilities, and generic rehabilitation programs. The study concludes that recidivist rehabilitation requires more personalized, structured, and collaborative strategies to fulfill the goals of the correctional system. The research offers theoretical contributions to the development of correctional law and provides practical recommendations for policymakers and correctional officers to strengthen individualized rehabilitation and enhance inter-agency coordination. Furthermore, it opens avenues for future studies on alternative rehabilitation models for high-risk recidivists.